Acclimation to NaCl and H2O2 develops cross tolerance to saline-alkaline stress in Rice (Oryza sativa L.) by enhancing fe acquisition and ROS homeostasis. Issue 3 (4th May 2022) - Kamanga, Rowland Maganizo; Oguro, Shohei; Nampei, Mami; Ueda, Akihiro
ABSTRACT: Plants are known to develop cross-tolerance in which plants tolerate to one stress following prior exposure to another stress. In this study, we investigated this phenomenon in rice ( Oryza sativa L.) to elucidate the underlying physiological mechanisms. Twenty-one (21) day-old seedlings were pre-exposed to various concentrations of NaCl, NaHCO3, and H2 O2 for 7 days and then subjected to saline-alkaline stress (SAS) for 14 days. The present findings report that pre-exposure to 10 mM NaCl and 10 µM H2 O2 develops cross-tolerance to SAS by triggering systemic physiological processes involved in Fe uptake and ROS homeostasis. While the mechanisms of this tolerance vary among pre-treatments, a consensus suggests the relevance of the following processes: (1) the ability to maintain a lower growth medium pH, (2) ability to suppress root K + losses, (3) maintenance of a stable acquisition of Fe and P and (4) regulated generation of reactive oxygen species (ROS) via enhanced antioxidant enzyme activities. Taken together, these results are consistent with the hypothesis that a crosstalk exists between salinity stress, oxidative stress, and SAS, triggering adaptive physiological responses that develop tolerance to SAS in rice, a phenomenon that offers a prospect for developing plants tolerant to multiple stressors.